Single pot transfer hydrogenation and aldolization of furfural over metal oxide catalysts - Biradar, Narayan S.; Hengne, Amol M.; Sakate, S. S.; Swami, R. K.; Rode, Chandrashekhar V. (Catalysis Letters, 2016)
One pot catalytic transfer hydrogenation (CTH) of furfural to furfuryl alcohol (FAL) by using hydrogen producing alcohols and simultaneous aldolization of carbonyl compounds produced during CTH, with furfural was achieved over non-noble metal oxides with bifunctional sites. Basic sites of MgO responsible for abstraction of proton showed complete conversion of furfural to give FAL and C8 monomer in a ratio of 3:1, respectively, the later altered to 1:1 by incorporating Al into MgO. Catalyst stability was established by its four cycles study. [GRAPHICS]
Keywords: Aldol; furfural; Furfuryl alcohol; Metal oxides; transfer hydrogenation

Maximization of furanic compounds formation by dehydration and hydrogenation of xylose in one step over SO3-H functionalized H-beta catalyst in alcohol media - Gupta, Anshita; Nandanwar, Sachin U.; Niphadkar, Prashant; Simakova, Irina; Bokade, Vijay (Biomass & Bioenergy, 2020)
Furanic compounds such as furfural (FUR); furfuryl alcohol (F. Alc) are important renewable platform chemicals can be used as such or further convert for preparation of other value added products such as Levulinic acid (LA), Alkyl Levulinates, 2-Methyltetrahydrofuran (MTHF), and Tetrahydrofuran (THF) etc. Sulfonated H-beta zeolite was successfully prepared and used for the synthesis of furanic compounds especially FUR and F. Alc from c-xylose in one step using isopropanol as alcohol media. Prepared catalyst was well characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), BET, NH3-Temperature programmed desorption (TPD) and carbon-hydrogen-nitrogen-sulfur analysis (CHNS). It was found the total acid amount was increased with increase in sulfur loading which confirmed the sulfonic acid group (SO3-H) was successfully grafted onto zeolite structure. 3 wt% H-beta-SO3-H catalyst with optimized reaction parameters of 150 degrees C, 7 h, 25 wt% catalyst loading was tuned to get the highest furanic compound yield of 88.5% (FUR 76.8% + F.Alc 11.7%).The reusability study confirmed that there was a marginal drop of similar to 25% after 3 recycle runs.
Keywords: furfural; Furfuryl alcohol; H-beta; isopropanol; sulfonated zeolite; Xylose

Synthesis of ethyl furfuryl ether (potential biofuel) by etherification of furfuryl alcohol with ethanol over heterogenized reusable H1Cs2PW12O40 catalyst - Mulik, Nagesh L.; Niphadkar, Prashant S.; Bokade, Vijay V. (Research on Chemical Intermediates, 2020)
{Ethyl furfuryl ether (EFE) considered as potential biofuel can replace petroleum diesel up to 100%. EFE also has efficient blending properties with biodiesel to improve its cold flow properties. Herein we demonstrate efficient synthesis of EFE by etherification of renewable furfuryl alcohol (FAlc) with ethanol over heterogenized heteropoly acids. Cs-exchanged heterogenized heteropoly acid (H3-xCsxPW12O40
Keywords: B; etherification; Ethyl furfuryl ether; Furfuryl alcohol; H3-xCsxPW12O40; Heterogenized heteropoly acid; L ration

Single-pot alcoholysis of furfuryl alcohol to alkyl levulinates using heterogenized p-TSA catalyst** - Patil, Chetana R.; Kamble, Sanjay P.; Rode, Chandrashekhar V. (ChemistrySelect, 2021)
Synthesis of levulinate esters which are known to be excellent sustainable fuel additives, was achieved by alcoholysis of furfuryl alcohol over strong solid acid catalyst, prepared by copolymerization of p-toluenesulfonic acid with paraformaldehyde. Our catalyst possessed Bronsted acidity (3 mmol/g) with an excellent stability up to 220 degrees C. XPS, FT-IR and Pyridine-IR along with microanalysis studies confirmed the presence of terminal -SO3H functional groups responsible for Bronsted acidity in the catalyst. The catalyst was found to efficiently catalyze the alcoholysis of furfuryl alcohol to give alkyl levulinates under mild reaction conditions. The complete conversion of furfuryl alcohol with 96 % and 97 % selectivities to ethyl and butyl levulinates could be achieved using ethanol and butanol, respectively. Detailed study on effect of various reaction parameters like catalyst loading, reaction time and reaction temperature on conversion and product distribution was also carried out for the ethanolysis of furfuryl alcohol to ethyl levulinate. The catalyst could be easily recovered and recycled for five times successfully, with no loss in its original activity.
Keywords: Biomass; ethyl levulinate; Fuel additive; Furfuryl alcohol; heterogeneous catalysis

Selective hydrogenation of furfural to furfuryl alcohol over Pd supported on ternary oxide in aqueous medium under mild conditions - Nehra, Pooja; Betsy, K. J.; Vinod, C. P. (ChemCatChem, 2025)
We report palladium (Pd) supported on a mixed CuO/ZnO/Al2O3 catalyst for the synthesis of furfuryl alcohol (FA) from furfural (FF) using hydrogen under near atmospheric pressure (balloon pressure) conditions. A systematic study of various metal oxide combinations revealed that the best support for Pd nanoparticles is a CuO/ZnO/Al2O3 mixed system, which results in excellent catalytic performance. A series of control experiments highlighted the essential role of mixed Cu-Zn-Al oxide support in facilitating the adsorption and activation of FF. Our results demonstrate that under optimal conditions (40 degrees C, balloon pressure H2), the catalyst yields FF conversion exceeding 98%, with remarkable selectivity for FA reaching up to 99% with water as solvent. The catalyst exhibited almost comparable activity up to three catalytic cycles without extra catalyst treatment or reactivation with negligible Pd leaching. These findings shed insight into the design of mixed metal oxide-based support for active metal interactions in optimizing catalytic performance in furfural hydrogenation under mild conditions.
Keywords: Biomass conversion; Furfural hydrogenation; Furfuryl alcohol; mixed metal oxides; Pd catalyst